Serological Survey of Dengue Virus Immunoglobulin M Among Febrile Patients in Kaduna Metropolis, Nigeria - Matthew O. Idoko; Saleh A. Ado; Veronica J. Umoh (Aceh International Journal of Science and Technology, 2014)
The purposes of this research were to determine the prevalence of dengue virus in the study population, to determine the relationship between the occurrence of dengue virus IgM and potential risk factors and to determine the association between the occurrence of dengue virus and some symptoms. In this study, blood specimen were collected from 340 subjects with febrile complaints attending hospitals in Kaduna metropolis, Nigeria and who gave their consent to participate. Serological determination of dengue virus IgM was carried out using enzyme linked immunosorbent assay technique. Structured questionnaires were also administered to obtain data on demographic, risk factors,  and symptoms of illness. A total of 6 subjects were positive for dengue virus IgM giving a prevalence of 1.8%. There was no statistically significant association between the occurrence of dengue virus IgM and potential risk factors, demographic factors and symptoms of the illness. The occurrence of dengue virus in the study population was confirmed.